2020
DOI: 10.1590/0101-60830000000236
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of neuropsychiatric and motor tests with language assessment in patients with Lewy body dementia

Abstract: Background: Lewy body dementia (LBD) impairs performance in daily activities and affects motor, language and visuospatial tasks. Objective: We aimed to correlate neuropsychiatric and motor assessments with language and visual organization tests in LBD. Methods: Twenty-two patients with dementia with Lewy bodies and ten patients with Parkinson's disease dementia participated on a cross-sectional study that assessed cognition, functionality, caregiver burden, verbal fluency, the primer-level dictation section of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, there can be no doubt that language and cognitive impairments are linked in DLB. 58 The nature and characteristics of the impairments affecting cognitive functions are relatively well established in the scientific literature. In contrast, the data on the deficits affecting the production and comprehension of language is less well developed.…”
Section: Discussionmentioning
confidence: 99%
“…However, there can be no doubt that language and cognitive impairments are linked in DLB. 58 The nature and characteristics of the impairments affecting cognitive functions are relatively well established in the scientific literature. In contrast, the data on the deficits affecting the production and comprehension of language is less well developed.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study exploring visuospatial dysfunctions in PD patients showed that 62.2% of 35 patients could not copy the pentagon drawing 26 . Moreover, Machado et al suggested that language and visual organization tend to follow motor skills and general cognitive performance in patients with DLB 27 . Poor cognitive performance frequently correlates with more advanced stages of the disease, older age, low schooling level, depression, and poorer quality of life 15 ),( 17 ),( 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in Brazil have assessed the cognitive profile of patients with PD using comprehensive and formal neuropsychological tests, such as the Mattis Dementia Rating Scale (MDRS), Scales for Outcomes in Parkinson’s Disease-Cognition (SCOPA-COG), Wisconsin Card Sorting Test (WCST), Frontal Assessment Battery (FAB), Verbal Fluency Tests 27 ),( 46 , and Trail Making tests 47 . A study applying a comprehensive neuropsychological battery showed cognitive impairment in 56.7% of PD patients in a waiting list for deep brain stimulation (DBS) implantation according to FAB scores and in 76.7% of them according to MoCA, showing the importance of a formal cognitive evaluation in this group of candidates to DBS 48 .…”
Section: Resultsmentioning
confidence: 99%